Multiple weak brakes act in concert to control STIM1 and store-operated calcium entry - Ruoyi Qiu; Richard S. Lewis (Proceedings of the National Academy of Sciences, 2025)
Store-operated Ca 2+ entry is a key signaling pathway controlled by the interaction of the ER Ca 2+ sensor STIM1 with the Orai1 Ca 2+ channel following ER Ca 2+ depletion. To avoid generating pathological effects, STIM1 must remain mostly inactive under resting, ER-replete conditions yet respond rapidly and reversibly to changes in ER Ca 2+ content. It is not well understood how these conflicting requirements are met. Here we combine single-molecule FRET measurements of full-length dimeric STIM1 in lipid membranes with an AlphaFold2 structural model to describe the structure and regulation of the resting state. We show that STIM1 activity is controlled by the combined operation of four relatively weak restraints, or brakes. The Ca 2+ -bound EF-SAM luminal domain acts as a steric restraint to inhibit spontaneous activity. In the cytosolic region, the domain-swapped hydrophobic interaction and alignment of CC1α1 with CC3 of the CRAC activation domain (CAD) positions the apex of CAD next to the ER membrane, where electrostatic lipid–protein interactions further stabilize the inactive conformation. A fourth brake is created by hydrophobic and electrostatic interactions of the two CC1α2/3 domains attached to the base of CAD. Disruption of any one of these brakes triggers spontaneous STIM1 activation, showing that the concerted action of these relatively weak restraints serves to minimize spontaneous activity in resting cells with full ER Ca 2+ stores, while allowing rapid activation in response to changes in store content.